Діаграма стану системи Mg–B при тиску 2 GPa - Туркевич, В.З.; Пріхна, Т.О.; Козирєв, А.В. (Физика и техника высоких давлений, 2008)
Методами гартування від високих тисків, рентгенівського аналізу і скануючої електронної мікроскопії проведено експериментальне вивчення фазових рівноваг в подвійній системі Mg–B при тисках 2–4 GPa. Експериментальні результати було використано для знаходження невідомих параметрів в феноменологічних моделях фаз, що конкурують при високих тисках. Виконано термодинамічні розрахунки і побудовано діаграму стану системи Mg–B при тиску 2 GPa. Система характеризується наявністю п’яти евтектичних рівноваг, при цьому бориди MgB₂, MgB₄, MgB₇ і MgB₂₀ плавляться конгруентно. Фаза MgB₁₂ під тиском 2 GPa є метастабільною. The quenching from high pressures, X-ray analysis, and scanning electron microscopy have been used to experimentally study phase equilibria in the Mg–B binary system at a pressure of 2–4 GPa. The experimental results have been used to define unknown parameters in phenomenological models of the phases competing at high pressures. Thermodynamic calculations have been made and the phase diagram of the Mg–B system at a pressure of 2 GPa has been constructed. The system is characterized by the presence of five eutectic equilibria. In this case, the MgB₂, MgB₄, MgB₇ and MgB₂₀ borides melt congruently. The MgB₁₂ phase is metastable at 2 GPa.